PERANCANGAN USER INTERFACE DAN USER EXPERIENCE APLIKASI MONITORING EXPIRED MENGGUNAKAN METODE DOUBLE DIAMOND - Restiani, Nala; Irmayanti, Dede; Andar Muni, Lise Sri (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Indomaret is one of the franchise business ventures which is a company owned by PT Indomarco Prismatama. At this time the process of monitoring products that are approaching the expiration date is still inefficient, often there are products whose expiration dates are missed and employees have difficulty finding products that will expire while there is no data and reminders about products that will expire. Therefore, a user interface design is needed before designing an application that can facilitate employees in managing expired products to be more efficient. In designing the user interface, researchers used the Double Diamond method which includes 4 stages, namely discover, define, develop, and deliver. For user experience testing, researchers adopted the User Experience Questionnaire (UEQ) method using 6 aspects with 26 items, including Attractiveness, Perpicuity, Effciency, Depandability, Stimulation, Novelty. The test results showed that t5 UEQ scales were on the "Excellent" assessment, namely on the Attractiveness, Efficiency, Dependability, Stimulation, Novelty scales. While one UEQ scale is at "Above Average", namely the Perspicuity scale.